Riqueza de la familia Orchidaceae en la zona de visitantes del Parque Nacional Cerro Azul Meámbar de Honduras - Wiese, Klaus W. (2015)
A list of orchids found in the visitors zone of Parque Nacional Cerro Azul Meámbar, Comayagua, Honduras, is presented. A monthly absence- presence matrix was made for the orchids found with flowers of each species; with this matrix we made a richness analysis using the first order jackknife estimator. The months of the year were grouped in function of the orchid species in flower for each month. More than 101 species of orchids are reported for the park, and 140 species are predicted for the visitor’s zone.